Polyoxometalate Functionalized Sensors: A Review - Veríssimo, Marta I. S.; Evtuguin, Dmitry V.; Gomes, M. Teresa S. R. (Frontiers in Chemistry, 2022)
Polyoxometalates (POMs) are a class of metal oxide complexes with a large structural diversity. Effective control of the final chemical and physical properties of POMs could be provided by fine-tuning chemical modifications, such as the inclusion of other metals or non-metal ions. In addition, the nature and type of the counterion can also impact POM properties, like solubility. Besides, POMs may combine with carbon materials as graphene oxide, reduced graphene oxide or carbon nanotubes to enhance electronic conductivity, with noble metal nanoparticles to increase catalytic and functional sites, be introduced into metal-organic frameworks to increase surface area and expose more active sites, and embedded into conducting polymers. The possibility to design POMs to match properties adequate for specific sensing applications turns them into highly desirable chemicals for sensor sensitive layers. This review intends to provide an overview of POM structures used in sensors (electrochemical, optical, and piezoelectric), highlighting their main functional features. Furthermore, this review aims to summarize the reported applications of POMs in sensors for detecting and determining analytes in different matrices, many of them with biochemical and clinical relevance, along with analytical figures of merit and main virtues and problems of such devices. Special emphasis is given to the stability of POMs sensitive layers, detection limits, selectivity, the pH working range and throughput.